Analisis Penerapan Aplikasi Akuntansi Berbasis Android Si Apik untuk Meningkatkan Kualitas Laporan Keuangan pada Tiga Sektor Usaha - Ningrum, Dewi Agustya; Fifiatul Nabila, Natasya Qisti; Wiraswati, Mitha Otik; Yuliansyah, Rizki Bachtiar (FAKULTAS EKONOMI UNIVERSITAS MAARIF HASYIM LATIF, 2024)
In the current digital era, it requires society to make changes because technological developments can be used to meet information needs. Technology has become part of society's need to obtain various information quickly and easily. Because the ease of information technology also has an impact on the financial sector. This research aims to determine the effectiveness of implementing the Si Apik application in improving the quality of financial reports in three business sectors. It is hoped that this research will help simplify the recording and preparation of financial reports and determine the effectiveness of implementing the Si Apik application in the three business sectors of manufacturing, trade and services. This research uses qualitative research methods with descriptive methods that apply data collection techniques, namely interviews, documentation and observation. The data sources for this research are primary and secondary data. Based on the research results, the